The Effects of Government Support, Social Support, and Self-Efficacy on Digital Business Performance: The Mediation Analysis of Social Media Adoption - Mohd Noor, Nurul Hidayana; Mohamad Fuzi, Amirah; Mohamad Fadzil , Nurin Farzana; El Ashfahany , Afief (Journal of Technology Management and Business, 2025)
Digital business is carried out using the Internet, providing many benefits to merchants and buyers. Business can be done 24 hours a day because the Internet is always present in human life and does not limit things like culture, race, distance, time, and country. Based on the theory of planned behavior (TPB) and guided empirical observations, this paper examines the determinants of predicting the performance of young entrepreneurs in digital business. This research uses primary data, where survey data are collected from 384 young entrepreneurs in Negeri Sembilan, Malaysia. The data analysis is based on structural equation modeling (SEM), operated with the IBM SPSS AMOS 26 program. The results found that the performance is driven by government support, social support, self-efficacy, and social media adoption. Second, social media adoption mediates the relationship between governmental support, social support, self-efficacy, and digital business performance. Therefore, it is hoped that this discussion will help the academic and practical fields understand this phenomenon and be used as a guide by policymakers to review the national digital business ecosystem and mechanism to further the development of young entrepreneurs. Technology has helped entrepreneurs reach the future of their business more efficiently and take the name of the business to a global level.